Implementasi Kurikulum Terpadu Model Integrated di SMP ISLAM IMAM ASY SYAFII KOTA METRO PROVINSI LAMPUNG - Adityo, Dimas; Pahrudin, Agus; Fauzan, Ahmad (UMSU, 2024)
Integrated learning is a learning process that combines various subjects in an effort to achieve desired competencies. The Integrated Learning curriculum is designed using an interdisciplinary approach by combining several fields of study. This study aims to understand and explain integrated learning with an integrated model at Imam Asy Syafii Islamic Junior High School in Metro City. The curriculum at Imam Asy Syafii Islamic Junior High School integrates three types of curricula, namely the Pure Arabic Language Curriculum (Silsilah li ta’lim Lughoh al Arabiyah), which is an Arabic language curriculum adopted from Imam Muhammad bin Saud Islamic University, Islamic Religious Education/Pondok Pesantren Special Diniyah Education, and the National Curriculum of the Education Department. This research is a qualitative descriptive study with data collection techniques using interviews, observations, and documentation. From the results of the research conducted, it can be concluded that: (1) Imam Asy Syafii Islamic Junior High School has implemented an Integrated Curriculum model by integrating several types of curricula to achieve competencies, namely Arabic language proficiency and knowledge of Islamic religion typical of pondok pesantren and general education. (2) Imam Asy Syafii Islamic Junior High School implements a boarding system. (3) Supporting and inhibiting factors for curriculum integration are divided into two, namely internal factors originating from within Imam Asy Syafii Islamic Junior High School and external factors from outside Imam Asy Syafii Islamic Junior High School.